Effect of Homeopathic Medicines on Intestinal Coccidia and Immune Response Cells in Spotted Rose Snapper (Lutjanus guttatus) - Rosero-García, Antonia del Pilar; Mazón-Suástegui, José Manuel; Dumas, Silvie; Chávez-Sánchez, María Cristina; Avilés-Quevedo, Araceli; Rodríguez-Jaramillo, Carmen (Homeopathy, 2019)
Background Homeopathy has been widely applied in freshwater species but rarely in marine fish. Farm stress destabilises host–pathogen equilibrium, favouring parasites and disease. Coccidian endoparasites cause intestinal infections and cell degeneration.Materials and Methods Naturally parasite-infested juvenile snapper Lutjanus guttatus (n = 430; weight 1.9 ± 0.01 g; length 4.9 ± 0.03 cm) specimens were distributed in group sizes of 43, in 10 fiberglass tanks (100 L) with aeration and continuous water change. Five groups in duplicate were assessed: Passival (PaV); Passival and Phosphoricum acid Similia (PaV–PhA); Passival and Silicea terra Similia (PaV–SiT); Endecto and Infecçoes (End–Inf) and a control (Ethanol) for 45 days. Feed was sprinkled with treatment (5% v/w) and dried to avoid ethanol side-effects. Statistical results were expressed as mean ± standard error of the mean.Results Intestinal coccidia were recorded histopathologically, with the least incidence attained at T45 with End–Inf treatment (p < 0.001), coinciding with the highest lymphocyte (p = 0.015) count. Fish treated with PaV–PhA recorded a higher percentage of neutrophils (p = 0.015), and those treated with PaV–PhA, PaV–SiT and End–Inf revealed a decrease in lesions, degree of alteration and change in intestine and stomach tissues (p < 0.05). The number of mucous cells in gills was greater (p < 0.001) for End–Inf (43 ± 0.58), PaV–SiT (40 ± 2.89) and PaV–PhA (39 ± 3.46) as compared respectively with T0 and control (19 ± 0.58 and 28 ± 2.31). PaV and PaV–SiT increased carbohydrate reserves in liver (28.4 ± 1.39% and 22.4 ± 0.12%, respectively) compared with T0 and control (3.4 ± 0.32 and 5.6 ± 0.66%). The highest survival rate was 97.7 ± 0.16% in fish treated with PaV and End–Inf.Conclusion Homeopathic treatments had a positive effect on fish health. Besides the accumulation of metabolic reserves in the liver, homeopathic treatment was associated with mucin increase in gills as well as raised production of lymphocytes and neutrophils in blood, which could act as macrophages against intestinal coccidia.
Keywords: aquacultural homeopathy; histopathology; endoparasites; blood cells; mucous cells